Effect of air humidity on the egg viability of predatory mites (Acari: Phytoseiidae, Stigmaeidae) common on rubber trees in Brazil - De Vis, Raf Michaël Julien; Moraes, Gilberto José de; Bellini, Marcos Roberto (Springer Nature, 2006)
Rubber pest mites, Calacarus heveae and Tenuipalpus heveae, reach economic damage levels at the end of the rainy season and the beginning of the dry season in Brazil. Therefore, low humidity adaptation might be an important characteristic for predatory mites to successfully control pest organisms. This study determined the effect of the relative humidity (RH) levels of 30-100% on the hatching of larvae of Amblyseius acalyphus, Euseius citrifolius, Iphiseiodes zuluagai, Metaseiulus camelliae, Agistemus floridanus and Zetzellia malvinae at 25 ± 0.5°C. These predatory mites are common on rubber trees in the state of São Paulo and might be used for introduction in the major rubber tree production regions in the state of Mato Grosso. At 70% RH or higher, viability was 70% or higher for all species, indicating that their performance might be higher during the rainy season than during the dry season. Eggs of E. citrifolius and M. camelliae presented higher viability at the lower relative humidity levels than those of other species, indicating that these species might have higher chance to persist in the dry season. It is suggested that M. camelliae should be further evaluated for introduction in the state of Mato Grosso, considering that this mite is not yet present in that area. © Springer 2006.
Keywords: Biological control; Euphorbiaceae; Hevea brasiliensis; Phytoseiidae; Relative humidity; Stigmaeidae; biological control; egg development; humidity; mite; predator; rubber; viability; animal; biological pest control; Brazil; female; growth, development and aging; Hevea; infestation; larva; parasitology; plant disease; Animals; Female; Humidity; Larva; Mite Infestations; Mites; Pest Control, Biological; Plant Diseases; Mato Grosso; South America; Acari; Agistemus floridanus; Amblyseius; Calacarus heveae; Euphorbia; Euseius; Metaseiulus; Tenuipalpus; Zetzellia